Implementasi Program Baznas Kota Balikpapan Dalam Pengembangan Pendidikan Agama Islam di STIT Balikpapan - Abd Rosyid; Asmaji Muchtar; Toha Makhsun (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
This research aims to explore the various programs implemented by BAZNAS Balikpapan City and to assess their impact on the advancement of Islamic Religious Education (PAI) at STIT Balikpapan. Employing a qualitative approach, the research utilizes data collection techniques such as interviews, observations, and documentation. The study's findings are carefully analyzed through several stages, involving data collection, reduction, compilation, and conclusion drawing.The results reveal that BAZNAS Balikpapan City's initiatives aimed at enhancing PAI at STIT Balikpapan encompass scholarships for the development of ulama, sports programs, educational training for community service, and research endeavors that have produced publications on zakat governance in Balikpapan City.Additionally, the implementation of these programs occurs through collaborative efforts. Notably, the ulama cadre program has been executed seamlessly, with eight STIT Balikpapan students awarded scholarships upon fulfilling specific requirements, including letters of recommendation from the heads of their respective Islamic boarding schools and confirmation of their enrollment at STIT Balikpapan. The sports and educational training programs were also successfully implemented, meeting expectations. Furthermore, the research initiative proceeded as planned, culminating in the publication of a book on zakat governance, representing the fruitful collaboration between BAZNAS Balikpapan City and STIT Balikpapan. In summary, this research indicates that the programs instituted by BAZNAS Balikpapan City, along with their effective implementation, have significantly enhanced the quality of PAI at STIT Balikpapan and provided notable benefits to the community.